Factors Affecting The Unemployment Rate In Takalar District - Hartati Hartati (Pustaka Digital Indonesia, 2021)
This study aims to determine the effect of the Minimum Wage, Population and Economic Growth on the Unemployment Rate in Takalar Regency. This research is limited by analyzing quantitative secondary data in the period between 2011-2020. The data is reprocessed according to the needs of the model used. The data source comes from the Central Statistics Agency (BPS Takalar. The research method used is multiple linear regression analysis with the help of SPSS 15. The results showed that the minimum wage variable (X1) had a negative and insignificant effect on the unemployment rate in Takalar Regency, the population variable (X2) had apositive and insignificant effect on the unemployment rate in Takalar Regency, and the economic growth variable (X3) had an insignificant effect on the unemployment rate. negatively and insignificantly to the unemployment rate in Takalar Regency.